Arbeitsbuch zu Finanzmanagement, Band I - Dettmer, Harald; Hausmann, Thomas; Himstedt, Ludwig; Steffens, Klaus-Dieter (Oldenbourg Wissenschaftsverlag, 2018)
Das Studien-, Übungs- und Arbeitsbuch zu "Dettmer. Hausmann, Finanzmanagement, Band 1"